Structural and stress analysis - Megson, T. H. G. (Elsevier Butterworth-Heineman, 2005)
Structural analysis is the corner stone of civil engineering and all students must obtain a thorough understanding of the techniques available to analyse and predict stress in any structure. The new edition of this popular textbook provides the student with a comprehensive introduction to all types of structural and stress analysis, starting from an explanation of the basic principles of statics, normal and shear force and bending moments and torsion. Building on the success of the first edition, new material on structural dynamics and finite element method has been included. Virtually no prior knowledge of structures is assumed and students requiring an accessible and comprehensive insight into stress analysis will find no better book available. * Comprehensive overview of structural and stress analysis * Invaluable to undergraduate civil engineers * Numerous worked examples and problems * Solutions manual available online.